Active management of severe hyponatraemia is associated with improved mortality. Issue 1 (January 2021) - Garrahy, Aoife; Cuesta, Martin; Murphy, Brian; O'Reilly, Michael W; Tormey, William P; Sherlock, Mark; Thompson, Chris J
Abstract : Objective: Severe hyponatraemia (plasma sodium concentration, pNa <120 mmol/L) is reported to be associated with mortality rates as high as 50%. Although there are several international guidelines for the management of severe hyponatraemia, there are few data on the impact of treatment. Design and methods: We have longitudinally reviewed rates of specialist input, active management of hyponatraemia, treatment outcomes and mortality rates in patients with severe hyponatraemia (pNa <120 mmol/L) in 2005, 2010 and 2015, and compared the recent mortality rate with that of patients with pNa 120–125 mmol/L. Results: Between 2005 and 2010 there was a doubling in the rate of specialist referral (32 to 68%, P = 0.003) and an increase in the use of active management of hyponatraemia in patients with pNa <120 mmol/L (63 to 88%, P = 0.02), associated with a reduction in mortality from 51 to 15% ( P < 0.001). The improved rates of intervention were maintained between 2010 and 2015, but there was no further reduction in mortality. When data from all three reviews were pooled, specialist consultation in patients with pNa <120 mmol/L was associated with a 91% reduction in mortality risk, RR 0.09 (95% CI: 0.03–0.26), P < 0.001. Log-rank testing on in-hospital survival in 2015 found no significant difference between patients with pNa <120 mmol/L and pNa 120–125 mmol/L ( P = 0.56). Conclusion: Dedicated specialist input and active management of severe hyponatraemia are associated with a reduction in mortality, to rates comparable with moderate hyponatraemia.